Strange harvest : organ transplants, denatured bodies, and the transformed self - Sharp, Lesley Alexandra (Berkeley : University of California Press, 2006)
Strange Harvest illuminates the wondrous yet disquieting medical realm of organ transplantation by drawing on the voices of those most deeply involved: transplant recipients, clinical specialists, and the surviving kin of deceased organ donors. In this rich and deeply engaging ethnographic study, anthropologist Lesley Sharp explores how these parties think about death, loss, and mourning, especially in light of medical taboos surrounding donor anonymity. As Sharp argues, new forms of embodied intimacy arise in response, and the riveting insights gleaned from her interviews, observations, and d.
We are the dead men -- Memory work -- Public encounters as subversive acts -- Human hybridity.
Includes bibliographical references (pages 269-298) and index.
Print version record.
JSTOR
Keywords: Transplantation of organs, tissues, etc. -- Social aspects -- United States; Medical anthropology -- United States; Ethnology -- United States; Funeral rites and ceremonies -- United States; Death -- United States; Mourning customs -- United States; Memorials -- United States; Kinship -- United States; Transplantation of organs, tissues, etc; Ethnology; Organ Transplantation; Tissue and Organ Procurement; Anthropology, Cultural -- United States; Tissue and Organ Procurement -- United States; Organ Transplantation -- United States; Anthropology, Cultural; United States; Greffe (Chirurgie) -- Aspect social -- États-Unis.; Anthropologie médicale -- États-Unis.; Ethnologie -- États-Unis.; Funérailles -- Rites et cérémonies -- États-Unis.; Mort -- États-Unis.; Deuil -- Coutumes -- États-Unis.; Monuments commémoratifs -- États-Unis.; Parenté -- États-Unis.; Greffe (Chirurgie); Ethnologie; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE -- Anthropology -- General; Transplantation of organs, tissues, etc; Death; Ethnology; Funeral rites and ceremonies; Kinship; Medical anthropology; Memorials; Mourning customs; Transplantation of organs, tissues, etc. -- Social aspects; United States; Bewältigung; Sozialanthropologie; Transplantation; Trauerarbeit; Trauerritual; Soziale Situation; Bestattungsritus; USA; Transplantatie; Anniversaries -- United States